GRÃOS; COMÉRCIO; INDÚSTRIA PETROQUÍMICA; FRUTICULTURA: v. 1 n. 2 (2016) - Coêlho, Jackson Dantas; Ximenes, Luciano Feijão; Viana, Fernando Luiz E.; Vidal, Maria de Fatima (Caderno Setorial ETENE, 2024)
.